MODEL DISTRIBUSI DIAMETER LIMA JENIS POHON PADA HUTAN TROPIKA BASAH DI KABUPATEN MAMUJU, SULAWESI BARAT - Beta Putranto (Forestry Faculty of Universitas Hasanuddin, 2010)
The objective of this research is to establish the most suitable tree diameter distribution model for five tree species on tropical rain forest in Mamuju District. This research was conducted on two locations. The 50 square plots were sampled systematically for seedling, sapling, pole and tree measurements of bintangur, jambu-jambu, lada-lada, matoa and nyatoh species. The distance among plots was 50 m. Variables to be measured were stem number of seedlings to trees and tree diameter at breast height (1,3 m) of saplings to trees. About 70% of the data were used to establish the best model, the rest of 30% were used to validate the model. Models to be analyzed were fourth-order semi-logarithmic transformed polynomial function, Weibull density function and monotonic decreasing Weibull function. The results show that the five tree species have a similar diameter distribution pattern. The shape of this distribution is the typical of uneven-aged stand distribution on natural forest, namely reversed J shape. The most suitable model for five species is second-order semi-logarithmic transformed polynomial function. Key words: model, diameter distribution, natural forest, uneven-aged stand.